2013
DOI: 10.1007/s12350-013-9676-4
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of cardiac SPECT performed at the primary care physician’s office

Abstract: Background. The prognostic value of single-photon emission computed-tomography (SPECT)-myocardial perfusion imaging (MPI) is well documented. However, the utility of SPECT-MPI when performed at a low-volume primary care physician's (PCP's) office is unknown.Methods. We conducted a prospective cohort study of consecutive patients referred by their PCP to undergo a stress-MPI at the PCP's office using a mobile laboratory. Major adverse cardiovascular events (MACE) of death, myocardial infarction (MI), and corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…[1][2][3][4][5][6] Numerous studies have demonstrated that abnormal MPI predicts a multifold increase in the risk of major adverse cardiac events (MACE). [1][2][3][4][5][6] Furthermore, the prognostic utility of MPI is incremental to clinical, treadmill stress test, and coronary angiography data. [7][8][9] The robust prognostic data, favorable diagnostic performance, and wide availability of SPECT-MPI have led to a great expansion in use with consequent excessive expenditure.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] Numerous studies have demonstrated that abnormal MPI predicts a multifold increase in the risk of major adverse cardiac events (MACE). [1][2][3][4][5][6] Furthermore, the prognostic utility of MPI is incremental to clinical, treadmill stress test, and coronary angiography data. [7][8][9] The robust prognostic data, favorable diagnostic performance, and wide availability of SPECT-MPI have led to a great expansion in use with consequent excessive expenditure.…”
mentioning
confidence: 99%
“…Hachamovitch et al [15] in a study involving 5,183 patients, followed by an average period of 642 days, showed that the annual rate of myocardial infarction was 0.5% in normal examinations, 2.7% had mild perfusion deficit, 2.9% for moderate deficit and 4.2% when there was severe impairment by SPECT. Doukky et al [16], in a study encompassing 1,390 followed by an average period of 27 months demonstrated that patients with perfusion deficits in mild to moderate magnitude showed HR for adverse events of 2.3 (95% CI 1.1-4.7, p = 0.02). On the other hand, non significant perfusion defects may be related to various clinical situations, such as the presence of endothelial dysfunction (an early marker of CAD), arrhythmias and myocardial hypertrophy without concomitant significant obstructive lesion, as well as a higher rate of equivocal studies due to attenuation artifacts, movement and gating, arrhythmias, conduction disturbances, errors of acquisition and post processing [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Two multivariable logistic regression models were fit to calculate the predicted probability of MACE (model 1) or revascularization within 6 mo (model 2) as determined by established clinical and imaging predictors (independent variables) known to affect these outcomes (1,9,12,16). The calculated probabilities of MACE were then annualized.…”
Section: Determination Of Predicted Probability Of Outcome Eventsmentioning
confidence: 99%
“…Myocar dial perfusion imaging (MPI) with SPECT is a pivotal tool in the risk assessment and clinical decision making in patients with known or suspected coronary artery disease (CAD) (1). The costly expansion in MPI use prompted professional organizations to develop appropriate use criteria (AUC) to guide physicians on the optimal use of SPECT MPI (2).…”
mentioning
confidence: 99%